Dietary behavior and knowledge of dental erosion among Chinese adults - Pang Karie KL; Chu CH; Lo Edward CM (BMC, 2010)
Abstract Objectives To study the dietary behavior and knowledge about dental erosion and self-reported symptoms that can be related to dental erosion among Chinese adults in Hong Kong. Methods Chinese adults aged 25-45 years were randomly selected from a list of registered telephone numbers generated by computer. A telephone survey was administered to obtain information on demographic characteristics, dietary habits, dental visits, and knowledge of and presence of self-reported symptoms that can be related to dental erosion. Results A total of 520 participants were interviewed (response rate, 75%; sampling error, ± 4.4%) and their mean age was 37. Most respondents (79%) had ever had caries, and about two thirds (64%) attended dental check-ups at least once a year. Respondents had a mean of 5.4 meals per day and 36% had at least 6 meals per day. Fruit (89%) and lemon tea/water (41%) were the most commonly consumed acidic food and beverage. When asked if they ever noticed changes in their teeth, most respondents (92%) said they had experienced change that can be related to erosion. However, many (71%) had never heard about dental erosion and 53% mixed up dental erosion with dental caries. Conclusion Hong Kong Chinese adults have frequent intake of food and many have experienced symptoms that can be related to dental erosion. Their level of awareness of and knowledge about dental erosion is generally low, despite most of them have regular dental check-ups. Dental health education is essential to help the public understand dental erosion and its damaging effects.